2016
DOI: 10.1002/ajim.22626
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the prevalence of musculoskeletal symptoms among female and male custodians

Abstract: Background The prevalence of musculoskeletal symptoms among custodians is high. We sought to compare musculoskeletal symptoms between female and male custodians and to explore how task might affect this relationship. Methods A cross-sectional study was performed among 712 custodians who completed a survey assessing upper extremity, back, and lower extremity musculoskeletal symptoms and exposure to cleaning tasks. Chi-square tests and logistic regression analyses were used to test for associations between gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
1
13
1
2
Order By: Relevance
“…The 12-month neck and low back pain prevalence rates of that study (69% and 65%, respectively) were higher than those of the present study, but this was expected given that dental students have relatively higher MSKP levels owing to their posture during practice [ 23 ]. Previous studies have found that females were more likely to suffer from MSKP than males, which was suggested to be due to their smaller body dimensions and lower muscle endurance [ 23 , 24 , 25 , 26 ]; however, this was not the case in our study, as MSKP equally affected about half of the male and female respondents at both analyzed timeframes.…”
Section: Discussioncontrasting
confidence: 85%
“…The 12-month neck and low back pain prevalence rates of that study (69% and 65%, respectively) were higher than those of the present study, but this was expected given that dental students have relatively higher MSKP levels owing to their posture during practice [ 23 ]. Previous studies have found that females were more likely to suffer from MSKP than males, which was suggested to be due to their smaller body dimensions and lower muscle endurance [ 23 , 24 , 25 , 26 ]; however, this was not the case in our study, as MSKP equally affected about half of the male and female respondents at both analyzed timeframes.…”
Section: Discussioncontrasting
confidence: 85%
“…The multivariable binary logistic regression showed that there was no significant association observed between sex, body mass index (BMI), physical exercise, and neck and upper limb MSDs. However, different studies reported the presence of gender difference in upper extremity MSDs among the working population in many occupational classes, with female workers having a higher risk [3840]. This difference might be due to the differences in the distribution of male and female workers in occupations with different risks for the neck and upper limb MSDs between countries.…”
Section: Discussionmentioning
confidence: 99%
“…O sexo feminino mostrou-se associado a DME nos três segmentos corporais estudados, corroborando demais estudos que abordam a temática 9,10,22,26,27 . Fatores como a dupla jornada de trabalho (que reduz o tempo para realização de atividade física ou relaxamento, limitando, dessa maneira, a prática de atividades que protegem das lesões e auxiliam na sua prevenção 10,28 ) e as diferenças antropométricas entre os sexos e entre as fibras musculares de homens e mulheres (que são mais fracas e menos resistentes) também podem contribuir para o surgimento de lesões musculoesqueléticas 29 .…”
Section: Discussionunclassified